How much did the February 6 earthquakes affect a distant hospital? - Koç, Miraç; Kukul Güven, Fatma Mutlu (MediHealth Academy, 2023)
Aims: In the earthquakes that took place in Kahramanmaraş on 06.02.2023, a large number of casualties and injuries were observed. Organizations and healthcare personnel providing healthcare services in the earthquake regions have significantly lost their functions and there have been disruptions in the provision of healthcare services. In this study, we analyzed the patients who applied due to being affected by the earthquake in Kastamonu, one of the provinces far from the epicenter of the earthquake. Methods: The records of 135 patients who admitted to Kastamonu Training and Research Hospital Emergency Medicine Clinic with the diagnosis of earthquake damage between 7-16 February 2023 were examined. They were divided into two groups: patients with trauma and other non-traumatic complaints. Demographic data, complaints, requested tests, final diagnoses, consultation and hospitalization status of the patients were recorded. Results: While 50 patients applied with complaints of trauma caused by the earthquake, 85 patients applied to the emergency department due to diseases other than trauma. 10 of these patients were hospitalized and the others were discharged. It was observed that soft tissue trauma was the most common diagnosis in applications for trauma reasons, and upper respiratory tract infection was the most common diagnosis for non-traumatic reasons. Conclusion: In our study, since we were a hospital far from the center of the earthquake, there were no patient applications on the first day, and since the patients arrived over the days, no problems arose during the triage and intervention stages.
Keywords: 3. Good health